The influence of speed of approach and accuracy constraint on the maximal speed of the ball in soccer kicking - Andersen, B.; Dörge, H. C. (Scandinavian Journal of Medicine & Science in Sports, 2011)
The kicking skill of the individual player is of great importance in soccer, and two parameters can be identified as being important in soccer kicking - achieving high speed of the ball and accuracy of performance. The purpose of the current study was to examine the influence of different speeds of approach on the maximal speed of the ball when kicking a stationary ball, and to examine the influence of accuracy of performance on the maximal speed of the ball relevant to a penalty kick. Seven male soccer players kicked for maximal speed of the ball (I) with a self-selected angle and speed of approach, (II) with accuracy demand placed on the subjects, (III) with a straight-line approach of different velocities ranging from 0 m/s to maximal running speed. The maximal speed of the ball was between 28.60 and 34.48 m/s. An accuracy constraint caused the speed of the ball to decline to 85%. With a straight-line approach, the maximal speed of the ball was between 25.64 and 32.26 m/s. When the subjects approached the ball at speeds other than the self-selected speed of approach, the speed of the ball declined, indicating a subject-specific optimal speed of approach.